Effects of glucose ingestion on fuel selection during cold exposure - Depault, Isabelle (University of Ottawa (Canada), 2009)
Recent studies of cold exposure have focused on the nutritional status of shivering individuals, studying the importance of carbohydrate stores for shivering muscles. These studies have illustrated that during moderate cold stress, muscle glycogen is the main substrate for heat production. Consequently, it is thought that shivering will cease and hypothermia will set in when muscle glycogen stores gets compromised or exhausted. In spite of this, no studies to date have investigated the effects glucose ingestion on fuel selection during cold exposure. Using a combination of indirect calorimetry and isotopic methods, the aims of this thesis were to determine the effects of glucose ingestion on whole body heat production and oxidative fuel selection to (1) confirm that heat production and core temperature will not change with glucose feedings during shivering, (2) quantify the effects of glucose feedings on whole body fuel selection, (3) quantify the effects of glucose feedings on the oxidation of CHO stores (muscle glycogen), and (4) quantify the oxidation of the ingested exogenous glucose. Six healthy men were exposed to cold for 120 min (liquid conditioned suit perfused with 4°C water) on three randomized occasions during which 500ml of a glucose solution was ingested to supply: 0.04 g·min-1 (C), 0.4 g·min-1 (Lo) or 0.8 g·min-1 (Hi) of glucose. We observed that (1) glucose ingestion has no effects on whole body thermal response. (2) Absolute and relative CHO and lipids oxidation rates did not differ significantly between conditions. (3) Muscle glycogen oxidation was not affected by glucose ingestion, but hepatic glucose production decreased with 0.8 g·min-1 of glucose ingestion. (4) The maximal rate of exogenous glucose oxidation observed was 0.2 g·min-1. No difference was seen between exogenous glucose oxidation rate during the Lo and Hi conditions. The result of this thesis provides the first estimates of exogenous glucose oxidation rate in the cold and quantifies the effects of glucose ingestion on whole-body energy demands. This information may contribute to improve survival strategies for human exposed to cold environments.
Keywords: Health Sciences, Recreation.; Biology, Physiology.